Coverage of insecticide-treated mosquito nets in preschool consultations and factors associated with non-use of insecticide-treated mosquito nets among children in the Democratic Republic of Congo: A base population cross-sectional study - Aliocha Natuhoyila Nkodila; Stanislas Okitasho Wembomyama; Reagan Okingo Luvande; André-Ronz Basilua Nsana; Philippe Ngwala Lukanu (PLoS ONE, 2026)
Insecticide-treated nets (ITNs) are among the most effective malaria prevention interventions, yet their actual use among children remains below national targets. This study assesses ITN coverage and utilization among children attending preschool consultations (PSC) and identifies factors associated with non-use. A cross-sectional study was conducted in 2025 in 156 health facilities across six provinces of the Democratic Republic of the Congo (DRC). Children aged 6–59 months accompanied by a parent or guardian were included. Data were collected during a household survey through face-to-face interviews using a structured questionnaire programmed in ODK Collect. Data on ITN ownership and use, as well as sociodemographic characteristics, were collected. Factors associated with non-use were analyzed using multivariate logistic regression. Among the 1,247 children included in preschool consultations, the mean age was 15.0 ± 4.3 months. The population showed marked socioeconomic vulnerability: 81.5% of guardians had a low educational level, 82.4% of households had low monthly income, and 48.2% lived in rudimentary housing. Community awareness through community health workers (CHWs) was high (78.7%). Overall, 62.5% of households owned at least one ITN, and 95.9% of children used it. The main factors associated with non-use were lack of community sensitization (aOR = 4.75), parental marital status (aOR = 4.57), rainy season (aOR = 3.41), rudimentary housing (aOR = 2.59), and a high number of children in the household (aOR = 1.80). Adherence to ITN use was ≥ 80% of individuals reporting sleeping under an ITNs the previous night, a predefined threshold based on WHO recommendations. Community-based interventions and context-adapted planning that account for seasonal and socioeconomic factors are essential to maximize the impact of malaria reduction among preschool children in the DRC.